Climate education in secondary science: comparison of model-based and non-model-based investigations of Earth's climate. Issue 13 (2nd September 2021) - Bhattacharya, Devarati; Carroll Steward, Kim; Forbes, Cory T.
ABSTRACT: In this mixed method study, we analyse the effectiveness of two pedagogical approaches – one model-based and another non-model-based – for developing secondary students' understanding of the phenomenon of increase in Earth's average surface temperatures, a core dimension of global climate change (GCC). Building on past research on teaching and learning about Earth's climate, we use an Evidence-Based Reasoning framework to assess student tasks and interviews from a 3-week, project-developed, model-based curriculum. We observed that the use of a climate model allowed students to reason more effectively about the Earth's increasing temperatures. They were able to establish the premise and interpret evidence for the phenomenon more effectively with the climate model. Using temperature and carbon dioxide data sets, students observed and quantified the behaviour of climate variables, establishing correlation and causation through data-integrated claims. In doing so, students were able to develop scientific knowledge about climate science as well as understand the processes undertaken by climate scientists in analysing climate data. Given the importance of fostering climate literacy in K-12 students, study findings have implications for both teaching and learning about GCC using climate models, as well as in shifting students' focus from acquiring knowledge to constructing their own knowledge.